Територіальна оборона в механізмі захисту Української держави: загальнотеоретичне дослідження : дисертація - Ярмола, С. О.; Yarmola, S. O.; Бойчук, А. Ю - науковий керівник (Харківський національний університет внутрішніх справ, 2024)
Дисертація є першим у правовій науці монографічним дослідженням територіальної оборони в механізмі захисту Української держави як невід’ємної складової механізму держави. У дисертації запроваджено загальнотеоретичний аналіз сутності територіальної оборони в механізмі захисту Української держави, як невід’ємної складової механізму держави. Розроблено поняття «механізм захисту держави» та обґрунтовано висновок про те, що механізм захисту держави – це складова механізму держави. Доведено, що механізм захисту держави включає таки елементи, як: 1) нормативно-правове регулювання забезпечення захисту держави; 2) інституційне забезпечення захисту держави; 3) заходи та способи створення умов для захисту держави; 4) принципи здійснення захисту держави. З’ясовано, що з позицій правової структуризації та систематики територіальна оборона України виглядає як комплексне утворення, правовий інститут. Обґрунтовано, що територіальна оборона України формується із трьох компонентів: а) військової складової; б) цивільної складової; в) військово-цивільної складової. Відстежено історію розвитку та сучасний стан територіальної оборони в Україні. Досліджено ознаки національної моделі територіальної оборони.. Проаналізовано особливості формування добровольчих формувань територіальної громади. Встановлено, що це чітко визначений порядок дій, в результаті чого формується повноцінне добровольче формування. Досліджено нормативну та функціональну основу територіальної оборони в Україні. Визначені шляхи та основні напрями поліпшення територіальної оборони в контексті завдань державно-правової реформи в Україні та напрацьовані пропозиції щодо удосконалення нормативних та інституційних засад функціонування національної моделі територіальної оборони. Проаналізовано зарубіжний досвід правової інституціоналізації і розвитку територіальної оборони в сучасних умовах.

The dissertation presents a general theoretical analysis of the territorial defense essence in the mechanism of the Ukrainian state protection as an integral part of the state mechanism. The concept of «State protection mechanism» has been developed and the conclusion that the State protection mechanism is a component of the State mechanism has been substantiated. It has been proven that the mechanism of State protection includes the following elements: 1) the normative and legal regulation of ensuring the protection of the State; 2) the institutional support for the protection of the State; 3) the measures and methods of creating conditions for the State protection. It has been established that the legal model of territorial defense in Ukraine is a set of legal provisions which define: 1) the essence and features of territorial defense as a socio-legal phenomenon with the distinction of general and special features; 2) the content of activities which constitute the essence of territorial defense; 3) the institutional mechanism of territorial defense which includes entities vested with the authority to implement the tasks of territorial defense; 4) the provision of territorial defense and its administrative direction. From the standpoint of legal structuring and systematics, it has been found that the territorial defense of Ukraine is a holistic entity, a legal institution. Furthermore, it has been substantiated that the territorial defense of Ukraine consists of three components: a) a military component; b) a civilian component; c) a military-civilian component. A history of development and the current state of territorial defense in Ukraine has been traced, which includes: 1) the Soviet period; 2) the period of Ukraine's independence: a) from 1991-2013 (accumulation of knowledge on territorial defense); b) from 2014-2021 (ATO, verification of knowledge on territorial defense); c) from 2022 to the present (war, standardization of knowledge on territorial defense).’ Particular features of the volunteer formations creation in the territorial community has been analyzed. The normative and functional basis of Ukrainian territorial defense has been studied. The ways and main directions of improving the territorial defense in the context of the state and legal reform tasks in Ukraine have been identified. These include: a) the gradual formation of an anti-corruption body specialized in territorial defense; b) the creation of mechanisms for controlling the expenditure of funds for territorial defense and the activities of territorial defense bodies; c) the development of measures for quality control in the procurement of defense goods, works and services, which will prevent abuse and unjustified expenditure of funds for defense needs; d) the further digitalization of territorial defense units, as well as the ensuring of cybersecurity and data protection. The foreign experience of legal institutionalization and development of territorial defense under current conditions has been analyzed. It has been proved that the model of Ukrainian defense as such directly covers the activities of all components of the security and defense sector of Ukraine, the unified civil protection system, local self-government bodies united by the goals and objectives, which exercise the legally established powers, functions and tasks to ensure preparation for defense, defense of the state, protection of its sovereignty and territorial integrity in the event of armed aggression.
Territorial defense in the defense mechanism of the Ukrainian state: a general theoretical study
Keywords: Дисертації. Theses. Диссертации; 12.00.01; територіальна оборона; захист держави; механізм; безпекове законодавство; модель територіальної оборони; військова доктрина; Збройні Сили України; військове командування; правовий режим воєнного стану; інституційна складова; Ukraine; territorial defense; state protection; mechanism; security legislation; model of territorial defense; military doctrine; Armed Forces of Ukraine; military command; legal regime of martial law; institutional component